Optimizing farmer capacity through improved group management and administration - Wardani, Ari Kusumah; Aziz, Saepul (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2025)
Building farmer groups has the potential to enhance both administrative and organizational management, as well as the technical aspects of agriculture. Weak institutional management can hinder the efficiency and effectiveness of farmer groups in carrying out agricultural activities. One of the weaknesses in the institutional management of farmer groups is related to the organizational structure, management, and coordination among group members. The Baleubat Dua farmer group in Cidewa Hamlet Dewasari Village Handap Herang District, Ciamis Regency is the object of community service activities related to institutional management of farmer groups with a total of 20 members of farmers and breeders. The method of approach is by conducting counseling and discussions related to the obstacles faced by farmer groups in terms of management and institutions that farmers want to know and the solutions provided to build more professional and competent farmer groups. The activity's outcomes demonstrated that participants were highly engaged in counselling activities, resulting in two-way contact between the communicator and the participants. The communicator's questions, suggestions, and productive conversations substantially aided this activity. The implementation of good management will strengthen collaboration among farmer group members and open up opportunities for diversification of farming businesses.